2022
DOI: 10.1051/0004-6361/202244391
|View full text |Cite
|
Sign up to set email alerts
|

Formation, distribution, and IR emission of dust in the clumpy ejecta of Type II-P core-collapse supernovae, in isotropic and anisotropic scenarios

Abstract: Large discrepancies are found between observational estimates and theoretical predictions when exploring the characteristics of dust formed in the ejecta of a core-collapse supernovae. We revisit the scenario of dust production in typical supernova ejecta in the first 3000 days after explosion, with an improved understanding of the evolving physical conditions and the distribution of the clumps. The generic, nonuniform distribution of dust within the ejecta was determined and using that, the relevant opacities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
(196 reference statements)
1
4
0
Order By: Relevance
“…The dust formation zone within the metal-rich ejecta is expected to be confined within 5000 km s −1 (Truelove & McKee 1999;Maguire et al 2012;Sarangi 2022), which is consistent with the velocity profile in Figure 2. These velocities correspond to a radius of ∼ 2.8 × 10 17 cm and 7.8 × 10 16 cm for SN 2004et and SN 2017eaw, respectively.…”
Section: Dust Origin and Heating Mechanismssupporting
confidence: 81%
See 3 more Smart Citations
“…The dust formation zone within the metal-rich ejecta is expected to be confined within 5000 km s −1 (Truelove & McKee 1999;Maguire et al 2012;Sarangi 2022), which is consistent with the velocity profile in Figure 2. These velocities correspond to a radius of ∼ 2.8 × 10 17 cm and 7.8 × 10 16 cm for SN 2004et and SN 2017eaw, respectively.…”
Section: Dust Origin and Heating Mechanismssupporting
confidence: 81%
“…Interestingly, we find that the total IR luminosity of SN 2004et is higher than the luminosity of SN 2017eaw, even though the latter is younger and is expected to have a stronger forward shock luminosity. This may indicate that the younger SN 2017eaw, being more compact, is optically thick in the mid-IR, as some theoretical studies suggest (Dwek et al 2019;Sarangi 2022). On the other hand, it may also indicate that the silicate-rich dust in the ejecta of SN 2017eaw is expanding at a smaller velocity (compared to carbon dust in SN 2004et), so a smaller fraction of the forward shock luminosity is absorbed here.…”
Section: Dust Origin and Heating Mechanismsmentioning
confidence: 81%
See 2 more Smart Citations
“…However, the composition of the dust close to the center is likely to differ from that of the outer regions (10). Dust nucleation models have predicted that silicates dominate over carbon-rich dust in the central regions (43)(44)(45)(46), of which Mg 2 SiO 4 (forsterite) is expected to have the highest abundance. Observations of young SNRs have shown that silicates are the dominant type of dust (10).…”
Section: Dust Effects On the Observed Emissionmentioning
confidence: 99%